Humans as prey: Coping with large carnivore attacks using a predator-prey interaction perspective - Penteriani V.; Bombieri G.; Fedriani J. M.; Lopez-Bao J. V.; Garrote P. J.; Russo L. F.; Delgado M. M. (2017)
The number of attacks on humans by large carnivores in North America is increasing.A better understanding of the factors triggering such attacks is critical to mitigating the risk offuture encounters in landscapes where humans and large carnivores coexist. Since 1955, ofthe 632 attacks on humans by large carnivores, 106 (17%) involved predation. We draw onconcepts and empirical evidence from the Predator–Prey Interaction Theory to provide insightsinto how to reduce predatory attacks and, thus, improve human–large carnivore coexistence.Because large carnivore-caused mortality risks for humans are comparable to those shown byother mammal species in response to predation risk, framing predatory attacks under a theoryunderpinning predator–prey interactions may represent a powerful tool for minimizing largecarnivore attacks. Most large carnivores have marked crepuscular and nocturnal activity; byminimizing outdoor activities in high-risk areas from sunset to sunrise, humans could reducethe number of predatory attacks. The most effective way in which prey avoid predation, butstill utilize risky areas, is by adopting temporal changes in activity patterns. The human agegroups most often targeted by large carnivores are essentially the same as when predators ingeneral search for prey, namely the youngest individuals. Thus, increased parental vigilanceand education for children may be a key factor to reduce predatory attacks. Lastly, becausegroup size can affect predator–prey encounter rates and outcomes in different ways, largegroups of people can decrease predation rates. Many humans may no longer considerpredation by large carnivores to be a logical or plausible consequence of our predator-naïvebehavior because humans now only occasionally represent prey for such species. However,the solution to the conflicts represented by large carnivore attacks on humans requires theimplementation of correct strategies to face these rare events